2020
DOI: 10.3389/fphys.2020.00085
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Restriction Changes the Expression of Fibroblast Growth Factor 23 and Its Receptors in Laying Hens

Abstract: Dietary phosphorus oversupply wastes non-renewable natural resources and raises environmental concerns in animal agriculture. We hypothesized that laying hens do not need large safety margins for dietary phosphorus because of the existence of fibroblast growth factor 23 (FGF23). In experiment 1, a total of 504 Hy-Line Brown laying hens (40-week-old) were randomly assigned to seven diets (for each diet, six replicates of 12 hens), containing 0.12, 0.17, 0.22, 0.27, 0.32, 0.37, and 0.42% non-phytate phosphorus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In addition, phytase, the most widely used dietary exogenous enzyme in animal production ( Adeola, 2011 ), breaks down phytate-phosphate from plant feed ingredients and dramatically reduces the animals' requirement for inorganic phosphorus ( Fernández et al., 2019 ). Interestingly, while the aforementioned technologies have repeatedly been documented in the literature, it still remains unclear in the field that how much inorganic phosphate rock will need be supplemented into poultry diets when those technologies are applied ( Li et al., 2015 , Adhikari et al., 2020 , Ren et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phytase, the most widely used dietary exogenous enzyme in animal production ( Adeola, 2011 ), breaks down phytate-phosphate from plant feed ingredients and dramatically reduces the animals' requirement for inorganic phosphorus ( Fernández et al., 2019 ). Interestingly, while the aforementioned technologies have repeatedly been documented in the literature, it still remains unclear in the field that how much inorganic phosphate rock will need be supplemented into poultry diets when those technologies are applied ( Li et al., 2015 , Adhikari et al., 2020 , Ren et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that dietary vitamin D 3 deficiency reduces the mRNA expression of FGFR (including FGFR1 , FGFR2 , FGFR3 and FGFR4 ) and VDR in the calvaria, but has no effect on the liver. Hepatic FGF23 mRNA expression is not sensitive to dietary phosphorus, nicotinamide and vitamin D 3 levels ( Ren et al., 2020b , 2020c ), suggesting that FGF23 may be related to other physiological functions in laying hens. Calvaria FGFR1 can sense changes in extracellular phosphorus levels and regulate the production of FGF23 ( Takashi et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Calvaria FGFR1 can sense changes in extracellular phosphorus levels and regulate the production of FGF23 ( Takashi et al., 2019 ). Similarly, serum phosphorus could change FGFR1 expression in the calvaria, which is an important factor in regulating the secretion of FGF23 ( Ren et al., 2020b ). It cannot be ignored that these receptors play an important role in osteogenic development, cartilage proliferation and bone loss, thereby regulating the calcium and phosphorus homeostasis of bones ( Arnold et al, 2021 ; Starczak et al., 2018 ; Xie et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations